An in vitro model of microbial contamination in the operating room. Issue 11 (27th May 2022) - Zhao, Wenhan; Libera, Matthew; Prysak, Meredith; Katz, Jordan; De Stefano, Lauren
Abstract: Infection associated with tissue‐contacting biomedical devices is a compelling clinical problem initiated by the microbial colonization of the device surface. Among the possible sources of contaminating bacteria is the operating room (OR) itself, where viable bacteria in the atmosphere can sediment onto a device surface intraoperatively. We have developed an aerosolizing system that can reproducibly spray small quantities of aerosolized bacteria onto a surface to mimic OR contamination. This paper describes the design of the system and characterizes key aspects associated with its operation. The area density of sprayed bacteria is on the order of 10 2 /cm 2 . Using titanium (Ti) alloy coupons as test substrates contaminated by staphylococci, we quantify the fraction of bacteria that are well adhered to the substrate, those that can be removed by sonication, and those that are not recovered after spraying. Despite the relatively low levels of surface contamination, we furthermore show that such a model is able to demonstrate a statistically significant reduction in colonization of Ti coupons modified by antimicrobial quaternary ammonium compounds relative to unmodified controls.